An-Niswiyah Fii Riwayah Banat al-Riyadh Li Raja’ Abdullah Al Sanea - Arika, Merdu; Ramadhani, Novi (Buletin Al-Turas, 2018)
This research is titled feminism in Banat al-Riyadh novel by Rajaa Al Sanea. This novel tells the lives of four women in the city of Riyadh who experienced injustice due to the rules of the family as well as from the government, which restricted the freedom of women; therefore I am interested in reviewing this title. This research focuses on one core problem: how to illustrate the feminism in the novel. The research method used in this research is descriptive method of analysis, and the results obtained from this study found some images of feminism; firstly, the desired freedom of women in this novel is to demand freedom in choosing a life partner, and freedom in social interaction. Secondly, education for women because women also have an important role for the progress of the nation, the advancement of a nation depends on the advance of education for women. Thirdly, a husband cannot divorce his wife unilaterally; there is a specific rule on this matter, so that women are not harmed by the situation.---Penelitian ini berjudul feminisme dalam novel Banat al-Riyadh karya Rajaa Al Sanea. Novel ini mengisahkan kehidupan empat perempuan di kota riyadh yang mengalami ketidakadilan yang disebabkan aturan dari keluarga maupun dari pemerintah, yang membatasi kebebasan perempuan, oleh karena itu saya tertarik mengkaji judul ini. Penelitian ini difokuskan pada satu permasalahan inti yaitu: bagaimana gambaran feminisme dalam novel. Adapun metode penelitian yang digunakan peneliti pada penelitian ini adalah metode deskriptif analisis dan hasil yang diperoleh dari penelitian adalah peneliti menemukan beberapa gambaran feminisme adalah pertama: kebebasan perempuan yang diinginkan novel ialah menutut kebebasan dalam memilih pasangan hidupnya, dan kebebasan dalam berinteraksi sosial. kedua: pendidikan bagi perempuan karena perempuan juga memiliki peran penting bagi kemajuaan bangsa, majunya suatu bangsa tergantung majunya pendidikan bagi perempuan. ketiga: talak bagi seorang suami tidak boleh menceraikan istrinya secara sepihak, ada aturan tersendiri mengenai hal ini, sehingga perempuan tidak dirugikan dengan situasi tersebut.DOI : 10.15408/bat.v24i1.6536